Elongation of textile pelvic floor implants under load is related to complete loss of effective porosity, thereby favoring incorporation in scar plates. Issue 4 (11th June 2013) - Otto, Jens; Kaldenhoff, E.; Kirschner‐Hermanns, R.; Mühl, Thomas; Klinge, Uwe
Abstract Use of textile structures for reinforcement of pelvic floor structures has to consider mechanical forces to the implant, which are quite different to the tension free conditions of the abdominal wall. Thus, biomechanical analysis of textile devices has to include the impact of strain on stretchability and effective porosity. Prolift® and Prolift + M®, developed for tension free conditions, were tested by measuring stretchability and effective porosity applying mechanical strain. For comparison, we used Dynamesh‐PR4®, which was designed for pelvic floor repair to withstand mechanical strain. Prolift® at rest showed moderate porosity with little stretchability but complete loss of effective porosity at strain of 4.9 N/cm. Prolift + M® revealed an increased porosity at rest, but at strain showed high stretchability, with subsequent loss of effective porosity at strain of 2.5 N/cm. Dynamesh PR4® preserved its high porosity even under strain, but as consequence of limited stretchability. Though in tension free conditions Prolift® and Prolift + M® can be considered as large pore class I meshes, application of mechanical strain rapidly lead to collapse of pores. The loss of porosity at mechanical stress can be prevented by constructions with high structural stability. Assessment of porosity under strain was found helpful to define requirements for pelvic floor devices. Clinical studies have to prove whether devices with high porosity as well as high structural stability can improve the patients' outcome. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1079–1084, 2014.